2015
DOI: 10.1586/17474124.2015.1004312
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mediterranean diet supplemented with silybin–vitamin E–phospholipid complex in overweight patients with non-alcoholic fatty liver disease

Abstract: We showed that the Mediterranean diet alone, or in association with the Realsil complex, led to the significant variation in BMI, waist circumference, total cholesterol and triglycerides. We also observed a statistically significant decrease in homeostasis model assessment technique in Group B patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 44 publications
5
43
1
1
Order By: Relevance
“…Four studies[8,39,40,45] reported blinding, describing methodological design as double-blind. Twelve studies[8,26-28,38-45] used only dry extract of Silybum marianum, which contains silymarin or silymarin alone, two[34,35] used silymarin associated with vitamin E and three[19,36,37] studies used silybin with vitamin E and phosphatidylcholine. All articles evaluated ALT, however the study by Velussi et al[26] only evaluated liver enzymes in the baseline, four[16,43-45] did not evaluate AST and eight[27-29,36,39,42-44] did not evaluate γGT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies[8,39,40,45] reported blinding, describing methodological design as double-blind. Twelve studies[8,26-28,38-45] used only dry extract of Silybum marianum, which contains silymarin or silymarin alone, two[34,35] used silymarin associated with vitamin E and three[19,36,37] studies used silybin with vitamin E and phosphatidylcholine. All articles evaluated ALT, however the study by Velussi et al[26] only evaluated liver enzymes in the baseline, four[16,43-45] did not evaluate AST and eight[27-29,36,39,42-44] did not evaluate γGT.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies[8,26-28,38-45] used only dry extract of Silybum marianum, which contains silymarin or silymarin alone, two[34,35] used silymarin associated with vitamin E and three[19,36,37] studies used silybin with vitamin E and phosphatidylcholine. All articles evaluated ALT, however the study by Velussi et al[26] only evaluated liver enzymes in the baseline, four[16,43-45] did not evaluate AST and eight[27-29,36,39,42-44] did not evaluate γGT. Six studies[26-28,36,37,39] did not report data on adverse effects, six[8,19,34,35,41,45] did not identify any of these effects, four[40-43] performed specific evaluation and only one[39] described that serious adverse events were not observed and that side effects were similar in frequency and uncommon in both groups.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, silibinin has been shown to ameliorate insulin resistance in HepG2 cells partially through targeting IRS‐1/PI3K/Akt pathway . From a clinical point of view, two small randomized clinical trials reported that supplementation of silibinin combined with phosphatidylcholine and vitamin E in patients with NAFLD may improve insulin resistance and liver histology as well as liver enzymes and lipid profile . Consistently, a silymarin‐vitamin E complex has been recently shown to reduce liver steatosis in a small uncontrolled clinical trial .…”
Section: Silymarin/silibininmentioning
confidence: 90%
“…However, this improvement was not accompanied by ALT reduction . Similarly, in a non‐randomized controlled trial among 20 NAFLD patients, MD improved the fatty liver index (FLI), but not liver enzymes . Conversely, in a quasi‐randomized trial, which evaluated the influence of different diets on liver enzymes, 259 obese diabetic patients have been assigned to either a diet recommended by the American Diabetes Association (50‐55% carbohydrate of mixed glycaemic index, 30% fat and 15‐20% protein), a low glycemic index (LGI) diet (50‐55% LGI carbohydrate, 30% fat, 15‐20% protein), or a modified (so that all foods will have low glycemic index) MD (35% LGI carbohydrate, 45% fats high in MUFA content, 20% protein), and found that despite the similar caloric content, the most significant reduction in ALT levels occurred in the modified MD arm at 6 and 12 months of follow‐up, even after adjustment for weight loss …”
Section: The Association Between the MD Pattern As A Whole And Nafldmentioning
confidence: 99%